Rancang Bangun Sistem Penyewaan di ESGO Media SMK Negeri 1 Godean menggunakan ISO 25010 - M. Royani Sopia Al Hasan; Arief Hermawan (Sekawan Institut, 2025)
State Vocational High School 1 Godean is a school with a center of excellence that has various facilities and activities that support learning activities for students. One way is by using the teaching factory method. One of the teaching factory methods at State Vocational High School 1 Godean is that there is a rental service for multimedia equipment and goods intended for students and general users outside State Vocational High School 1 Godean called ESGO Media. There are problems experienced by ESGO Media in rental activities, one of which is the occurrence of human errors such as data input errors which make the data invalid and cause problems when you want to use it. The aim of this research is to develop a Web-based rental information system at ESGO Media State Vocational High School 1 Godean and test the information system with the ISO 25010 standard. The development method used is the Research and Development method with an Agile model with design through data flow diagrams. This research produced a Web-Based Rental Information System at ESGO Media with the results of obtaining a score of 100% in the functional suitability aspect with a very good category for use, 87.65% in the usability aspect and getting a very suitable for use category. In the reliability aspect, it gets an average test score of 77%, has a performance score of 70.48% and is categorized as grade C in the performance efficiency aspect, and is categorized as a system that is easy to maintain based on the maintainability aspect with a maintainability index value of 39.82 . It is hoped that this information system can improve performance and make it easier for ESGO Media managers to carry out rental activities at ESGO Media and become a basis for developing information systems in the future.